CASE STUDY ON CURRICULUM IMPLEMENTATION 2013 IN SOME MADRASAH ALIYAH IN WEST KALIMANTAN PROVINCE - Ahmad Dudin (Sekretariat Badan Litbang dan Diklat Kementerian Agama RI, 2018)
English This paper is the result of a case study in 2016. The study was overshadowed by the implementation of the 2013 curriculum in Islamic Senior High School (Madrasah Aliyah). It was conducted in several Madrasah Aliyahs in the Province of West Kalimantan. The data and information were collected using qualitative-evaluative study through qualitative and descriptive approach. The study is mainly based on some accounts of various parties involved in the implementation of the 2013 curriculum (K.13), such as the primciples, teachers, supervisors and madrasah committees. The findings of this research indicate that the implementation of K.13 in the provincial office of Ministry of Religious Affairs as the pilot project in 19 MAs is a priority, but the second policy after the issuance of the General Director of Islamic Education Regulation no. 482 Th. 2015 on the peer Madrasah for the implementation of K.13 in the academic year 2014/2015. However, this initiative needs to consider the level of readiness among the MAs in the province due to the unavoidable local obstacles. Indonesia Tulisan ini merupakan hasil studi kasus tahun 2016. Latar belakang dari studi kasus ini adalah adanya persoalan implementasi kurikulum 2013 di Madrasah Aliyah, yang menuntut perbaikan. Studi ini mengambil kasus di beberapa MA di Propinsi Kalimantan Barat. Data dan informasi diperoleh melalui studi kualitatif evaluatif, dengan pendekatan kualitatif dan deskriptif. Hasil studi ini, merupakan penilaian atau pendapat dari berbagai pihak yang terlibat dalam implementasi kurikulum 2013 pada beberapa MA di Propinsi Kalimantan Barat, seperti kepala MA, guru, pengawas, dan komite madrasah.Temuan penelitian ini menyebutkan bahwa kebijakan implementasi K.13 di Wilayah Kementerian Agama Kalimantan Barat, untuk pilot project terhadap 19 MA, adalah prioritas, namun kebijakan kedua setelah diterbitkannya Peraturan Dirjen Pendis Kemenag No. 482 Th. 2015 tentang Penetapan Madrasah Pendampingan K.13, maka Tahun Pelajaran 2014/2015 memberlakukan K.13 namun keberadaanya perlu ditopang kesiapan yang matang mengingat dalam implementasi K.13 se Kalbar banyak ditemui kendala.